Kandungan Bahan Kering Tanpa Lemak (BKTL) Susu Sapi Perah Friesian Holstein Akibat Pemberian Pakan yang Mengandung Tepung Katu (Sauropus androgynus (L.) Merr) yang Berbeda - Roosena Yusuf (Journal of Tropical Pharmacy and Chemistry, 2012)
The purpose of this research was to determine the effect of increasing the provision shrub on milk solid non fat content of Friesian Holstein dairy cattle. Research material used was 9 Friesian Holstein dairy cattle on the second lactation at the sixth month lactation with body weight (BW) of 436 Â± 48.67 kg, milk production of 8.86 Â± 1.2 liter. Single factor experiment arranged in Complete Random Design with 3 treatments, each replicated for three times, was used in this experiment. The cows were fed with concentrate feed (Crude Protein = 13.42%) added by shrub flour at three levels of 0 % BW (t0), 0.03 % BW (t1), 0.05 % BW (t2), and maize straw as forage at each level of shrub flour in the concentrate. The ratio between concentrate and forage 60%:40%. Obtained data was calculated by ANOVA. Results showed that the average consumption of dry matter feed determined at t0, t1, and t2 were 10.22; 10.70 and 11.63 kg/cow/day (P>0.05), respectively. The average of milk solid non fat of t0, t1 and t2 were 0.672; 0.811 and 0.864 kg/liter (P>0.05), respectively. However shrub flour providing in the concentrate until level of 0.05% BW did not increase milk solid non fat of Friesian Holstein dairy cattle milk solid non fat. Keywords : milk solid non fat, Friesian Holstein dairy cattle, shrub